2000
DOI: 10.1038/82630
|View full text |Cite
|
Sign up to set email alerts
|

Absence of perilipin results in leanness and reverses obesity in Leprdb/db mice

Abstract: Obesity is a disorder of energy balance. Hormone-sensitive lipase (HSL) mediates the hydrolysis of triacylglycerol, the major form of stored energy in the body. Perilipin (encoded by the gene Plin), an adipocyte protein, has been postulated to modulate HSL activity. We show here that targeted disruption of Plin results in healthy mice that have constitutively activated fat-cell HSL. Plin -/- mice consume more food than control mice, but have normal body weight. They are much leaner and more muscular than contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
438
7
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 541 publications
(482 citation statements)
references
References 16 publications
31
438
7
6
Order By: Relevance
“…Activation of, or overexpression of, HSL prevents TG accumulation in adipocytes (Sztalryd et al, 1995). Perilipins, which are phosphoproteins coating the surfaces of lipid droplets of adipocytes, have been postulated to modulate HSL activity (Martinez-Botas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of, or overexpression of, HSL prevents TG accumulation in adipocytes (Sztalryd et al, 1995). Perilipins, which are phosphoproteins coating the surfaces of lipid droplets of adipocytes, have been postulated to modulate HSL activity (Martinez-Botas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in perilipin knockout mice have established an important role for perilipins in regulating lipolysis in adipocytes, and hence, controlling the mass of triacylglycerol deposited in adipose tissue (10,11). The mechanisms by which perilipins maintain control of adipocyte triacylglycerol metabolism are poorly understood, although recent mutagenesis studies have identified structural motifs important to perilipin function in triacylglycerol storage and lipolysis (12)(13)(14)(15)(16)).…”
mentioning
confidence: 99%
“…Das Vorhandensein der PAT Proteine an Lipidtropfen scheint für Li pidtropfen essenziell zu sein, da der Ver lust von Adipophilin und Perilipin im Mausmodell organspezifisch eine drasti sche Reduktion der Lipidtropfen bewirkt [3,11]. Offenbar können verschiedene PAT Proteine sich nur bedingt gegensei tig kompensieren.…”
Section: Diskussionunclassified